Use of ATLANTIS TIERRA 2.0 in mapping the biodiversity (invertebrates and bryophytes) of caves in the Azorean archipelago - Borges, Paulo A. V. (2013)
XII International Symposium on vulcanospeleology. Tepoztlan, Morelos, Mexico, July 2-7, 2006.